The Comedy of absurd - how an architect read Beckett's reading of Dante (Živi jezici: Journal for Foreign Languages and Literatures, 2022)
This paper interprets an architectural project from David Bilobrk’s Master's studies, The Comedy of Absurd (2013), but due to the many facets of this architectural solution, it also enters the spheres of literary criticism and literary history. The project that is submitted to hermeneutic study is in its essence hermeneutic, having in mind that it contains evident prototexts – Dante’s Divine Comedy and the works of Beckett – which are implicitly interpreted through the architectural expression. The third intertextual link is of theatrological nature due to the fact that, in a sense, the project finds its explication in postdramatic theatre. The final result of Bilobrk’s exploration is essentially humanistic insofar as The Comedy of Absurd testifies to contemporary human existence.
Keywords: Divine Comedy; Samuel Beckett; theatre of absurd; postdramatic theatre; architecture